The impact of globalization, renewable energy, and labor on sustainable development: A cross-country analysis - Huynh Ngoc Chuong; Vo Tran Phuong Uyen; Nguyen Dang Phuong Ngan; Nguyen Thi Bao Tram; Nguyen Dao Mai Han; Pham Hoang Khanh Duyen (PLoS ONE, 2025)
Sustainable development stands as both a goal and a prevailing trend in the global economy all the time. However, a comprehensive understanding of the internal and external determinants influencing sustainable development is necessary for the formulation of appropriate policies and development strategies. This research investigates dimensions of sustainable development in the panel data of 104 selected countries from 2000 to 2020. These economies are categorized into four groups based on the level of development. The exclusive role is given to the impact of three key factors, based on the triple bottom line (TBL) model, such as globalization, labor, and renewable energy on sustainable development. We employ the panel unit root tests, cointegration tests, and pool mean group (PMG) approach to estimate the relationships between globalization, renewable energy, labor force, and sustainable development. The results indicate the positive effects of globalization, labor, and renewable energy on sustainable development. Furthermore, a higher level of renewable energy consumption promotes sustainable development within the divided groups. The findings highlight that the labor factor has a positive impact on the sustainable development of all groups of economies. Thereby, the sustainability policy are implied to focus on the educational policy, improving social stability and renewable energy sources, particularly in the middle trap countries.